Virulence assessment of enterohepatic Helicobacter species carried by dogs using the wax moth larvae Galleria mellonella as infection model. Issue 4 (21st April 2021) - Ochoa, Sofía; Fernández, Fabiola; Devotto, Luis; France Iglesias, Andrés; Collado, Luis
Abstract: Background: Enterohepatic species of the genus Helicobacter (EHH) are emerging pathogens that have been associated with gastrointestinal and hepatobiliary diseases in humans. However, studies on their pathogenicity are scarce. Galleria mellonella is a recently proposed model for the study of virulence in different pathogens, such as Campylobacter spp. and Helicobacter pylori . Despite this, its usefulness in EHH has not yet been evaluated. Therefore, we determined the pathogenic potential of different EHH species isolated from dogs in this infection model. Materials and Methods: Four species of EHH ( H . bilis, H . canicola, H . canis, and 'H. winghamensis') isolated from fecal samples from domestic dogs were evaluated. Three strains of each species were inoculated in cohorts of G . mellonella at a concentration of 1 × 10 7  CFU/mL. Survival curves were determined by the Kaplan‐Meier method. In addition, the quantification of melanin, bacterial load in hemolymph, and histopathology were evaluated daily post–infection (pi). Results: G . mellonella larvae are susceptible to EHH infection, exhibiting intra‐ and inter‐species variability. Melanin production became evident from 4 h pi and increased throughout the assay. All species were recovered from the hemolymph after 20 min pi; however, only H . canis could be recovered up to 48 h pi. Histopathology revealed cellular and humoral immune response, evidencing accumulation of hemocytes, nodulation, and melanin deposition in different tissues. Conclusion: EHH species carried by dogs have considerable pathogenic potential, being H . canicola the species with the highest degree of virulence. Thus, G . mellonella is a useful model to assess virulence in these emerging pathogens.